The Political Portraits of the Leaders Struggling for the Unification of Italy in the Newspaper “Mshak” - Movsisyan, Feliks; Brutyan, Mariya (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
During that period, both the Armenian public opinion and the periodical press exhibited a profound understanding of the Italian Risorgimento. They accurately perceived the fundamental objectives driving the Italian people’s struggle. From the outset of the conflict, their publications consistently emphasized the liberation motive behind the Italian movement. They astutely acknowledged its aim to liberate itself from foreign rule, abolish the entrenched political fragmentation, promote national unity, and establish a united Italian state. Viewed from this perspective, the Risorgimento is vividly portrayed through the “Mshak” newspaper, published in Tiflis in 1872, under the editorial guidance of Grigor Artsruni, who was a leading voice of his time. Artsruni deemed one of the primary objectives of his newspaper to be the coverage of 19th-century European political events, along with the promotion of civilization, progress, enlightenment, scientific, and cultural achievements. This dedication is evidenced by the regular reporting of the global political events in the latter part of the 19th century within the pages of the “Mshak.” While documenting the European political transition, Artsruni adhered to the principle: “The political morality of the 19th century is this: “I rebel, so I am.” With this mindset, G. Artsruni's perspective on the unification of Italy, already a historical reality during the publication of his newspaper, becomes evident. The editor of the “Mshak” harbored immense interest in the success of the Italian liberation struggle and the leaders of the Risorgimento. Any relevant reference will attest to their pivotal role in securing the independence and freedom of their homeland. According to Grigor Artsruni, “Nowhere did the national idea find such resolute and courageous advocates, nowhere did the populace sympathize and engage in the movement to free the motherland from foreign oppression as much as in Italy.” “Nowhere did the people endeavor to unify the disparate parts of the nation to the extent seen in Italy.” Газета «Мшак», рупор армянского либерального движения, дает вполне реалистическую оценку лидерам борьбы за объединение Италии. Газета называет Дж. Мадзини идеологом Рисорджименто, создавшим тайную организацию «Молодая Италия» с целью освобождения родины и составившим программу освобождения страны, согласно которой планировалось провозгласить Италию республикой. Хотя Дж. Мадзини не удалось объединить Италию, тем не менее он сыграл значимую роль в объединении патриотических сил и в руководстве национальной борьбой. Ис-ходя из этих реалий, «Мшак» считает Дж. Мадзини выдающимся республиканцем, демократическим гением и великим патриотом. «Мшак» особо отмечает вклад Дж. Гарибальди в борьбу за объединение Италии. Газета характеризует его как великого итальянского патриота, храброго военачальника, бессмертного полководца, непобедимого борца, истинного народного героя, увековечившего свое имя заслугами перед Родиной. Согласно материалам газеты, патриотизм и честность Дж. Гарибальди, его готовность пожертвовать собой ради независи-мости Родины вызывают всеобщее уважение. Именно такие патриоты и герои решают судьбу своей нации. Газета называет Дж. Гарибальди героем, какового давно не было в истории, а его смерть считает на-циональной трагедией Италии. Газета «Мшак» характеризует Виктора Эммануила II как видного государственного деятеля, патриота и храброго воина, короля, кото-рый руководствовался исключительно интересами народа и государст-ва. Монарх надеялся на успешный исход борьбы Дж. Гарибальди, чтобы присвоить его победу. Таким образом он объединил Италию, что считал целью своей жизни. Посему Виктор Эммануил II занимает особое место в истории Италии. Հայ լիբերալ հոսանքի գաղափարակիր «Մշակ» թերթը Իտալիայի միավորման համար պայքարի առաջնորդներին բավական իրատեսական գնահատական է տալիս։ Թերթը Ջ․ Մացցինիին անվանում է Ռիսորջիմենտոյի գաղափարախոս, ով իր հայրենիքն ազատագրելու նպատակով ստեղծեց «Երիտասարդ Իտալիա» գաղտնի կազմակերպությունը, կազմեց հայրենիքի ազատագրության ծրագիր, որը նախատեսում էր Իտալիան հռչակել հանրապետություն։ Նա, թեպետ, չկարողացավ միավորել Իտա-լիան, բայց նշանավոր դեր խաղաց հայրենասիրական ուժերի համախմբման ու ազգային պայքարի ղեկավարման գործում։ Ելնելով այս իրողությունից՝ «Մշակը» Ջ․ Մացցինիին Մացցինիին համարում է երևելի հանրապետական, ժողովրդավարական հանճար և մեծ հայրենասեր։ «Մշակը» Ջ․Գարիբալդուն բնութագրում է որպես իտալական մեծ ազգասեր, երևելի հայրենասեր, քաջ զորավար, աշխարհաճանաչ անմահ զորապետ, աննկուն մարտիկ, իսկական ժողովրդական հերոս, ով իր անունն անմահացրեց հայրենիքին մատուցած ծառայություններով։ Նրա ազգասիրությունը, հայրենասիրությունը, հայրենիքի անկախության համար զոհաբերվելու պատրաստակամությունը և ազնվությունը ամենայն հարգանք են առաջացնում ազգային հերոսի նկատմամբ։ Ջ․ Գարիբալդու նման երևելի ազգասերներն ու հերոսները վճռում են իրենց ժողովրդի բախտը, ներկայացնում են այդ ժողովրդի ծնունդն ու պատկերը։ Այդ իմաստով Ջ․ Գարի-բալդին մարդկության պատմության մեջ վաղուց ի հայտ եկած հերոս է։ «Մշակի» բնութագրմամբ՝ Վիտտորիո Էմմանուել II-ը ազգասեր և երևելի պետական գործիչ էր, հայրենասեր և քաջ զինվորական, ժողովրդի ու պետության շահով առաջնորդվող թագավոր։ Նա գաղտնի ուրախությամբ սպասում էր Ջ․ Գարիբալդու պայքարի հաջողությանը և տեր դառնում նրա հաղթանակին։ Այդ ճանապարհով նա միավորեց Իտալիան, ինչը համարում էր իր կյանքի նպատակը, ուստի Վիտտորիո Էմմանուել II-ի անունը փառավոր տեղ է գրավում Իտալիայի պատմության մեջ։
Keywords: History